Uptake Within Achilles Tendon on Posttherapy Radioiodine Whole-Body Scan Related to Gouty Tophus. (August 2020) - Ehrhart, Mark; Tulchinsky, Mark; Blacklock, Lisa C.; Elojeimy, Saeed
Abstract : Abstract: A 66-year-old man with history of papillary thyroid cancer status post total thyroidectomy underwent 131 I-radioiodine ablation. Posttherapy 131 I whole-body scan revealed unexpected activity within the left posterior ankle. SPECT/CT localized the radioiodine uptake to a gouty tophus in the Achilles tendon.